The essence and peculiarities of the development of industrial marketing in Ukraine - Shkvyrya, Natalya (Видавництво Львівської політехніки, 2013)
In article the nature and meaning of industrial marketing in market conditions are determined. The main differences between consumer marketing of industrial marketing are systematized. Prerequisite for the development of industrial marketing in Ukraine are identified.
Keywords: Industrial marketing; industrial market; consumer marketing; need; demand; marketing activities